Exploitation of Lactic Acid Bacteria and Baker’s Yeast as Single or Multiple Starter Cultures of Wheat Flour Dough Enriched with Soy Flour - Teleky, Bernadette-Emőke (Biomolecules, 2020)
Sourdough fermentation presents several advantageous effects in bread making, like improved nutritional quality and increased shelf life. Three types of experiments aimed to evaluate comparatively the efficiency of two Lactobacillus (Lb.) strains, Lb. plantarum ATCC 8014 and Lb. casei ATCC 393, to metabolize different white wheat flour and soybeans flour combinations to compare their efficiency, together with/without Saccharomyces cerevisiae on sourdough fermentation. For this purpose, the viability, pH, organic acids, and secondary metabolites production were investigated, together with the dynamic rheological properties of the sourdough. During sourdough fermentation, LAB presented higher growth, and the pH decreased significantly from above pH 6 at 0 h to values under 4 at 24 h for each experiment. Co-cultures of LAB and yeast produced a higher quantity of lactic acid than single cultures, especially in sourdough enriched with soy-flour. In general, sourdoughs displayed a stable, elastic-like behavior, and the incorporation of soy-flour conferred higher elasticity in comparison with sourdoughs without soy-flour. The higher elasticity of sourdoughs enriched with soy-flour can be attributed to the fact that through frozen storage, soy proteins have better water holding capacity. In conclusion, sourdough supplemented with 10% soy-flour had better rheological properties, increased lactic, acetic, and citric acid production.